Biological Nanocarriers in Cancer Therapy: Cutting Edge Innovations in Precision Drug Delivery - Ramesh Ganpisetti; Sanjay Giridharan; G. S. Sainaga Jyothi Vaskuri; Nikesh Narang; Pratap Basim; Mehmet Remzi Dokmeci; Menekse Ermis; Satish Rojekar; Amol D. Gholap; Nagavendra Kommineni (Biomolecules)
Cancer is a highly detrimental and fatal illness that poses a significant threat to human well-being. The pattern of cancer treatment is continuously being optimized by the advancement of old treatment approaches and the invention of novel treatment modes. Nanotechnology-based approaches are emerging as powerful candidates in the development of these advanced methods for treating tumors. This article provides a concise overview of nanotechnology for cancer or cancer nanomedicine and its applications. In light of prevalent issues, such as inadequate precision in targeting initial chemotherapy drugs, susceptibility of nucleic acid drugs to degradation, gene delivery, and the occurrence of common immune-related adverse events during immunotherapy, we explore the potential integration of nanomedicine with these treatment approaches and illustrative examples and highlight the benefits that arise from the utilization of nanomedicine.